2014
DOI: 10.1186/1471-2407-14-974
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of urokinase-type plasminogen activator system components in clear cell renal cell carcinoma patients without distant metastasis

Abstract: BackgroundMembers of the urokinase-type plasminogen activator (uPA) system including uPA, its receptor uPAR and the plasminogen activator inhibitor 1 (PAI-1) play an important role in tumour invasion and progression in a variety of tumour types. Since the majority of clear cell renal cell carcinoma (ccRCC) shows distant metastasis at time of diagnosis or later, the interplay of uPA, uPAR and PAI-1 might be of importance in this process determining the patients’ outcome.MethodsCorresponding pairs of malignant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…One earlier study on ccRCC using immunohistochemistry also reported that PAI-1 was associated with tumor stage and disease progression [31], which is in line with our findings. Furthermore, we found that high PAI-1 mRNA as well as PAI-1 protein levels were associated with poor survival of the patients, confirming the independent survival information previously reported [29, 30]. The association between PAI-1 and tumor progression might be due to the regulation of angiogenesis by PAI-1 [30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One earlier study on ccRCC using immunohistochemistry also reported that PAI-1 was associated with tumor stage and disease progression [31], which is in line with our findings. Furthermore, we found that high PAI-1 mRNA as well as PAI-1 protein levels were associated with poor survival of the patients, confirming the independent survival information previously reported [29, 30]. The association between PAI-1 and tumor progression might be due to the regulation of angiogenesis by PAI-1 [30].…”
Section: Discussionsupporting
confidence: 88%
“…In breast cancer, it has a pivotal role in tumor vascular remodeling and neovascularization [25]. Expression of PAI-1 promotes cancer progression and high levels of PAI-1 proteins are associated with poor survival in some malignancies [2629]. In ccRCC, high PAI-1 expression is correlated with a high nuclear grade, an advanced stage, distant metastasis, and shortened disease-free survival [30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis differed and found that KLK1 , KLK2 , KLK3 , KLK4 and KLK15 are highly upregulated in chromophobe renal cell carcinoma. We hypothesize that the increase in these five kallikreins may cause increased expression of uPA and the destruction of the ECM, which has been shown to be active in renal carcinoma [ 37 39 ]. KLK5 and KLK6 are decreased in all three types of the renal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The level of uPA receptor expression correlated with the density of blood vessels in tumors and poor prognosis of the disease [28, 29]. In renal cancer, high levels of uPA and uPAR in tumor tissue extracts are associated with a significantly shorter survival of ccRCC patients though without distant metastases [30]. These data indicate the importance of uPA regulated by tumor associated macrophages in the reorganization of the vascular system of the tumor.…”
Section: Tumor Associated Macrophages Origin and Functionmentioning
confidence: 99%